2012
DOI: 10.1074/jbc.m111.310888
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of ATP Binding Cassette Transporter A1 Expression by Very Low Density Lipoprotein Receptor and Apolipoprotein E Receptor 2

Abstract: Background: VLDLR and apoER2 are receptors for reelin and apoE. Results: Reelin or apoE3 induced macrophage ABCA1 expression and increased cholesterol efflux. Down-regulation of VLDLR, apoER2, or inhibition of Dab1, PI3K, PKC and Sp1 attenuated reelin-or apoE3-induced ABCA1 expression. Conclusion: Activation of VLDLR-and apoER2-mediated signaling up-regulates ABCA1 expression. Significance: Up-regulation of ABCA1 expression is a novel function of VLDLR and apoER2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…In addition to adipocytes, VLDLR is also expressed in immune cells, including macrophages (22,23), but it is not known whether it regulates adipose tissue remodeling in obesity. In this study, we investigated the role of VLDLR in obesityrelated adipose tissue inflammation and adipocyte-macrophage interaction.…”
mentioning
confidence: 99%
“…In addition to adipocytes, VLDLR is also expressed in immune cells, including macrophages (22,23), but it is not known whether it regulates adipose tissue remodeling in obesity. In this study, we investigated the role of VLDLR in obesityrelated adipose tissue inflammation and adipocyte-macrophage interaction.…”
mentioning
confidence: 99%
“…[53][54][55] More recently, activation of the VLDL receptor and the apoE receptor 2 have also been shown to increase ABCA1 mRNA levels and protein expression, as well as cholesterol efflux to apoA-I. 56 Conversely, macrophage ABCA1 gene expression and the efflux of cholesterol to apoA-I are suppressed by members Figure 2. Biogenesis of spherical high-density lipoproteins (HDLs).…”
mentioning
confidence: 99%
“…86 Activation of apoE receptor 2 (apoER2) following treatment of mouse macrophages with human apoE3 significantly increased ABCA1 mRNA and protein levels via the activation of the PI3K-PKCζ-Sp1 signaling cascade. 85 Furthermore, in vivo activation of apoER2 on mouse brain capillaries by elevated levels of apoE in the brain parenchyma, as a result of methamphetamine treatment, increased the expression of ABCB1 and reduced the expression of ABCC1 at the brain capillaries through the apoE/apoE receptor-2/c-Jun N-terminal kinase 1/2 pathway. 86 Modulation of ABCA1 expression and/or activity is, thus, expected to influence apoE/Aβ interactions along with Aβ deposition and consequent undesirable effect in the brain.…”
mentioning
confidence: 99%
“…79 This study found that Aβ binding to apoE4 redirected the rapid clearance of free Aβ from LRP1 to the VLDL receptor, which internalized apoE4 and Aβ-apoE4 complex at the BBB more slowly than LRP1 compared to apoE2 and apoE3 and their Aβ complexes which cleared much faster via both VLDLR and LRP1. 79 Findings from recent studies have shown that apoE may play role in regulation of ABCA1 85 and the ABC transporters ABCB1 and ABCC1. 86 Activation of apoE receptor 2 (apoER2) following treatment of mouse macrophages with human apoE3 significantly increased ABCA1 mRNA and protein levels via the activation of the PI3K-PKCζ-Sp1 signaling cascade.…”
mentioning
confidence: 99%